Current guidelines for malaria treatment in Somalia: evidence-based recommendations - Warsame, Marian; Abdulrahman Osman, Ali; Hussein Hassan, Abdikarim; Abdulle, Abdi; Muse, Abdikarim; Mohamed Hassan, Abdilahi; Abdullahi Ali, Mohamed; Essa Yusuf, Fahmi; Hefzullah Amran, Jamal (Somali Health Action Journal, 2021)
Case management – rapid diagnosis and prompt administration of artemisinin-based combination therapy (ACT) – is a fundamental pillar of recommended malaria interventions in Somalia. Unfortunately, the emergence and spread of drug resistant falciparum parasites continues to pose a considerable threat to effective case management. With technical and financial support from WHO, the efficacy of recommended ACTs has been regularly monitored in sentinel sites since 2003. These studies provided evidence that supported the adoption of artesunate-sulfadoxine/pyrimethamine as first-line treatment in 2005 and artemether-lumefantrine as second-line treatment in 2011. Efficacy studies conducted between 2011 and 2015 showed high artesunate-sulfadoxine/pyrimethamine treatment failure rates of 12.3% - 22.2%, above the threshold (10%) for a change of treatment policy as recommended by WHO. This was also associated with high prevalence of quadruple and quintuple mutations in the dihydrofolate reductase (Pfdhfr) and dihydropteroate synthase (Pfdhps) genes, which are associated with sulfadoxine/pyrimethamine resistance. Based on these findings, national malaria treatment guidelines were updated in 2016, with artesunate-sulfadoxine/pyrimethamine replaced by artemether-lumefantrine as first-line treatment and dihydroartemisinin-piperaquine recommended as second-line treatment. Subsequent efficacy studies in 2016 and 2017 confirmed that both the current first- and second-line treatments remain highly efficacious (cure rate above 97%). Technical and financial support from WHO has been instrumental in generating evidence that informs malaria treatment policy and should therefore continue to ensure that effective treatments are available to malaria patients in the country.